THE EFFECT OF ORGANIC MATTER AND PLANTING TIME IN INTERCROPPING SYSTEM OF PEANUT AND MAIZE - Sarjoni Sarjoni (Pusbindiklat - LIPI, 2013)
Intercropping system is a double cropping, involving the growing of two or more crops sequentially or delaying of growing period of a crop. Effect of intercrop competition on the utilization of solar radiation, water, mineral nutrients, and space to grow can cause yield losses. This study was aimed to evaluate the effect of organic matter and planting time in intercropping system of peanut and maize on growth and yield. The research was carried out at the Experimental Farm of Haluoleo University in 2008 and was laid out in a Split Plot Design with three replications. The treatment consisted of two factors, organic matter as main plot and planting time as subplot. Results showed that interaction between organic matter and planting time had significant effect on seed number of maize, pod number of peanut , weight of 100 seeds of peanut, and yield and harvest index of maize and peanut.